'Essential and undervalued: health disparities of African American women in the COVID-19 era'. Issue 1 (2nd January 2021) - Obinna, Denise N.
ABSTRACT: Objectives: Transforming the landscape of American healthcare, COVID-19 has had unprecedented effects on the African American community. African Americans are more likely to contract COVID-19, develop complications and die from the virus. Amid the growing research on COVID-19, this manuscript pays particular attention to African American women who are disproportionately represented as 'essential' or frontline workers, yet often lack job security and risk contagion. Faced with limited testing centers, they are also at risk of having their symptoms minimized or dismissed by medical practitioners even when they show visible symptoms of COVID-19. Methods: Using the theoretical framework of intersectionality developed by scholars like Kimberlé Crenshaw and Patricia Hill Collins, this manuscript examines the impact of COVID-19 on African American women. It emphasizes that African American women are vulnerable to COVID-19 due to the twin legacies of racism and sexism. Intersectionality theory espouses that racism and sexism often combine with social determinants of health such as economic stability and socio-environmental factors to shape health outcomes. Within the context of COVID-19, this work underscores that African American women are susceptible to the virus due to their higher likelihood of co-morbidities like obesity, diabetes and high blood pressure. They are also likely to face eviction and homelessness if they are laid off or furloughed as a result of the pandemic. Conclusion: This manuscript asserts that decades of racism and discrimination have isolated communities of color and made them particularly vulnerable to the COVID-19 virus. As many African American women deal with unemployment or continue to work as 'essential workers', the intersectionality framework sheds light on the continued legacies of racism and sexism. It asserts that targeted policy interventions are needed to mitigate the effects of COVID-19 and lessen the devastating impact(s) it has had on African American communities.